GE_GERICHTE C/11568/2017 vom 7. September 2021 - GE Cour de justice (2021)
ENTENF;Loyer hypothétique;frais de parascolaire;frais de loisirs;frais extraordinaires (orthodontiques);REVHYP | CC.276.al1; CC.276.al2; CC.285.al2; CC.286.al3